ACCOMPANIEMENT FOR NEWLY RECRUITED TEACHERS IN THE POST-PANDEMIC CLASSROOM: EXPERIENCE, TEMPORALITY, COMPLEXITY & SINGULARITY - Mounir MILOUDI (Universitaria Publishing House, Craiova, 2024)
Remote support training for newly recruited university teachers has been adopted by the supervisory authority in Algeria during the post-pandemic period. This system represents an invitation to teachers to renew their modes of action and redefine their practice. This training approach also represents a real online learning platform that encourages exchanges between teachers and students, as well as collaboration and mutual support between students. The substance of our contribution aims to highlight our experience, in this context, to create an online course entitled "Observation of Pedagogical Practices" on the Moodle platform, with new learning strategies. Positive feedback from testers confirms the success of this new educational approach. Via this device, we were able to improve our technical skills by exploiting a variety of media available to us. This support was an experience of educational assistance and a real situation of using the platforms. It allowed us to combine collaborative activities with more individualized learning, customizing learning paths to student needs. Moreover, it helped us to develop our spirit of synthesis, thus allowing the students to learn without being constrained to go frequently to the university.